2004
DOI: 10.1002/aic.10003
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of buoyancy driven bubbly flow: Established simplifications and open questions

Abstract: An assessment is given of the present state of modeling and simulation of buoyancy driven gas-liquid bubble flow based on the two-fluid approach. Main points of discussion

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
219
1
9

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 304 publications
(239 citation statements)
references
References 71 publications
10
219
1
9
Order By: Relevance
“…T h i s f o r c e wa s n eg l e c t e d i n a l l t h e p r ev i o u s simulations in accordance with the observations made by Hunt et al 33) , Thakre and Joshi 2) , Deen et al 5) , and Sokolichin et al 4) . The turbulent dispersion force, derived by Lopez de Bertodano 34) is based on the analogy with molecular movement.…”
Section: Conservation Of Momentumsupporting
confidence: 89%
See 1 more Smart Citation
“…T h i s f o r c e wa s n eg l e c t e d i n a l l t h e p r ev i o u s simulations in accordance with the observations made by Hunt et al 33) , Thakre and Joshi 2) , Deen et al 5) , and Sokolichin et al 4) . The turbulent dispersion force, derived by Lopez de Bertodano 34) is based on the analogy with molecular movement.…”
Section: Conservation Of Momentumsupporting
confidence: 89%
“…Amongst the such as limited range of applicability of the empirical aforementioned approaches, the two-fluid approach is correlations so developed, difficulty in extrapolating the widely used. Although there are several studies in inferences to other geometries or even scaled-up versions context of turbulent bubbly flows, a large number of of the same equipment, and overall cost and time frame these studies are found on gas-liquid systems (Friberg 1) ; limitations have led to more attention being focused on Thakre and Joshi 2) ; Joshi 3) ; Sokolichin et al 4) ; Deen et numerical approaches such as computational fluid al. 5) ; Dhotre and Joshi 6) ).…”
Section: Introductionmentioning
confidence: 99%
“…According to the suggestion made by Sokolichin et al [24], neglecting the lift force can still lead to satisfying results if no clear experimental evidences for its direction and magnitude are available. They also pointed out that the effect of virtual mass force is negligible except for high frequency fluctuations of the slip velocity.…”
Section: (3) Interphase Momentum Exchangementioning
confidence: 99%
“…After the initial instability of the solution, the second order upwind for the momentum and turbulence terms, as well as the Quick scheme for the volume fraction, were utilized to increase the accuracy of the solution. For the time discretization, the first order implicit scheme was used because of the sufficient accuracy of its results in the ALRs (Sokolichin and Eigenberger, 2004).…”
Section: Model Solution Proceduresmentioning
confidence: 99%